Urban solid waste in the southern of Rio Grande do Sul state - Hoss, Louise; Santos, Natali Rodrigues dos; Demarco, Carolina Faccio; Dall’ Agnol, Ana Luiza Bertani; Loebens, Larissa; Quadro, Maurizio Silveira; Andreazza, Robson; Corrêa, Érico Kunde (Ciência e Natura, 2019)
The National Solid Waste Policy creates tools for the correct management of waste, such as municipal solid waste management plans. Thus, the aim of this study was to evaluate the generation of municipal solid waste and public management policies in municipalities in the Southern Zone of the state of Rio Grande do Sul. Fourteen municipalities were analyzed, where the data of urban and rural population, population served, amount of annual waste collection, annual per capita generation, amount of recycled waste and the final disposal site of the wastes were collected. The municipality with the lowest percentage of collection coverage was Pedras Altas with a value of 35.1% and the highest was Pelotas, with a value of 96.55% collection coverage. Only 50% of the municipalities analyzed have an agreement with recycling cooperatives or associations. The city of Morro Redondo has the highest recycling rate, of 16.25%. Regarding the final disposal, most of the municipalities carry out the outsourcing of this service, and only the municipality of Chuí has its own sanitary landfill.